Integration of Language and Mathematical Intelligence in Improving Elementary School Students' Literacy - Sitompul, Ismaini; Rais, Muhammad Amien; Sitompul, Nurul Hadawiyah (Yayasan Zia Salsabila, 2025)
Elementary school students' literacy levels are often separated between language skills and mathematical reasoning, resulting in partial and less impactful improvement efforts. This research aims to systematically examine evidence on the integration of language and mathematical intelligence to improve elementary school students' literacy. The method used was a systematic literature review (SLR) based on PRISMA guidelines, searching Scopus, WoS, ERIC, and Google Scholar databases with combinatorial keywords such as